1999
DOI: 10.1590/s0103-90161999000400010
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do estádio de desenvolvimento da antera e da radiação gama na formação de calos derivados de anteras de tomate

Abstract: Este trabalho foi conduzido visando: (I) determinar a influência do estádio de desenvolvimento de anteras de tomate sobre a formação de calos e (II) analisar o efeito da radiação gama no cultivo in vitro de anteras. No primeiro experimento, anteras de híbridos de tomate IPA 5 x Rotam 4 (F1) foram cultivadas em três meios nutritivos. Apesar da formação de calos ter sido induzida em todos os estádios de desenvolvimento, variando de prófase I à micrósporo mononucleado, a freqüência de calos produzidos decresceu c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Anthers containing microspores, obtained from buds with length ranging from 5.0 to 5.9 mm, did not respond to in vitro induction. Other studies corroborated that meiocytes is the most responsive stage for tomato anther culture (Zamir et al, 1980;Summers et al, 1992;Brasileiro et al, 1999;Seguí-Simarro and Nuez, 2005). Gresshoff and Doy (1972), Summers et al (1992) and Brasileiro et al (1999) reported that anthers showed higher frequencies of callus production during prophase I.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Anthers containing microspores, obtained from buds with length ranging from 5.0 to 5.9 mm, did not respond to in vitro induction. Other studies corroborated that meiocytes is the most responsive stage for tomato anther culture (Zamir et al, 1980;Summers et al, 1992;Brasileiro et al, 1999;Seguí-Simarro and Nuez, 2005). Gresshoff and Doy (1972), Summers et al (1992) and Brasileiro et al (1999) reported that anthers showed higher frequencies of callus production during prophase I.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, we show that flow cytometry can be a useful tool to screen the developmental stage of anthers. Brasileiro et al (1999) also analyzed the correlation between tomato anther length and meiotic phase. These authors reported that flower buds of size 5.0 to 6.0 mm and anthers of size 2.0 to 2.3 mm showed cells in meiosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many crops, the stage near to the first mitosis has been considered the most inductive (Peters et al, 1999). Secale cereale (Wang et al, 2000) and Brassica oleraceae (Kameya and Hinata, 1970) are exceptions in which the pollen grains must be with the starch deposition and Arabidopsis thaliana (Gresshoft and Doy, 1972) and Lycopersicon escutelum (Brasileiro et al, 1999) that must be at meiosis. For cereals the optimal developmental stages are mid to late uninucleate, in barley and wheat, and late uninucleated and early binucleated for rice and maize (Jähne and Lörz, 1995).…”
Section: Introductionmentioning
confidence: 99%